PANDANGAN MASYARAKATBTERHADAP SITUS PENINGGALAN MEGALITIKUM SARKOFAGUS DI KABUPATEN SAMOSIR - Sinaga, Menanti; Bedriati, Bedriati; Ahmal, Ahmal (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Sarcophagus is a large stone tomb has existed since megalithic era. Sarcophagus are often found in Samosir regency. This study exims to (1) determine the origin of sarchopaghus in Samosir, (2) to find out the spread of sarcophgus in Samosir, (3) to find out the spread sarcophagus megalithic heritage site in Samosir, (4) to find out the offer of the goverment to preserving sarcophagus in Samosir, in this study the author used a qualitable descriptive method. Qualitative descriptive method is a method that clims to describe with words about something or objects based on facts that exist in the present. Data colleded through the method of abservation, interviews, and documentation. Data analysis use 3 components, namely data reduction, data presentation and data verifcation. The time of study began from the submission of the proposal title to the competion of the thesis writing he result of this study are found in different people?s views of the sarcophagus.Key Words: Sarcophagus Megalithic In Samosir Regency